Association of CSF soluble TREM1 levels with hippocampal atrophy in cognitively impaired older adults - Hao Shu; Gangyu Ding; Xiaona Xu; Xuerong Huang; Ruqian He (Frontiers in Aging Neuroscience)
BackgroundRecent studies have shown that cerebrospinal fluid (CSF) levels of soluble triggering receptor expressed on myeloid cells 1 (sTREM1) are elevated in individuals with Alzheimer’s disease (AD), though the relationship between CSF sTREM1 and hippocampal atrophy remains to be elucidated. The primary aim of this study was to investigate the association between CSF sTREM1 levels and longitudinal changes in hippocampal volumes, and to determine if this relationship is moderated by cognitive status.MethodsWe included 576 participants, comprising 152 cognitively unimpaired (CU) and 424 cognitively impaired (CI) individuals. In the cross-sectional analyses, Pearson’s correlation tests were conducted to examine the relationship between baseline CSF sTREM1 levels and hippocampal volumes in both CU and CI participants. For the longitudinal analyses, a linear mixed-effects model was employed to assess the significance of the three-way interaction between CSF sTREM1 levels, cognitive status, and follow-up time on adjusted hippocampal volume (aHV). Further stratified analyses based on cognitive status were performed to dissect the specific effects within each group.ResultsOur findings revealed significantly elevated baseline CSF sTREM1 levels in CI participants compared to CU participants. Cross-sectional analyses demonstrated that CSF sTREM1 levels were negatively associated with hippocampal volumes in both CU and CI participants. In the longitudinal analyses, the three-way interaction between CSF sTREM1 levels, cognitive status, and follow-up time was found to be significant for aHV. Stratified analyses indicated that, in CI participants, higher CSF sTREM1 levels were associated with a more accelerated rate of hippocampal atrophy, whereas no such association was observed in CU participants.ConclusionThese results underscore the complex interplay between neuroinflammation, as reflected by CSF sTREM1 levels, hippocampal atrophy, and cognitive decline. The data suggest that neuroinflammation may contribute differently to hippocampal atrophy rates in CI versus CU individuals, highlighting the potential for targeted anti-inflammatory interventions in the prevention and treatment of AD.